Prevalence and correlates of sleep disorders in Parkinson’s disease: a polysomnographic study - Vanessa Alatriste-Booth; Mayela Rodríguez-Violante; Azyadeh Camacho-Ordoñez; Amin Cervantes-Arriaga (Arquivos de Neuro-Psiquiatria)
Objective Sleep disorders in Parkinson’s disease are very common. Polysomnography (PSG) is considered the gold standard for diagnosis. The aim of the present study is to assess the prevalence of nocturnal sleep disorders diagnosed by polysomnography and to determine the associated clinical factors. Method A total of 120 patients with Parkinson’s disease were included. All patients underwent a standardized overnight, single night polysomnography. Results Ninety-four (78.3%) patients had an abnormal PSG. Half of the patients fulfilled criteria for sleep apnea-hypopnea syndrome (SAHS); rapid eye movement behavior disorder (RBD) was present in 37.5%. Characteristics associated with SAHS were age (p = 0.049) and body mass index (p = 0.016). Regarding RBD, age (p < 0.001), left motor onset (p = 0.047) and levodopa equivalent dose (p = 0.002) were the main predictors. Conclusion SAHS and RBD were the most frequent sleep disorders. Higher levodopa equivalent dose and body mass index appear to be risk factors for RBD and SAHS, respectively.